2010
DOI: 10.1083/jcb.201006049
|View full text |Cite
|
Sign up to set email alerts
|

Cep152 interacts with Plk4 and is required for centriole duplication

Abstract: Cep152, the orthologue of Drosophila Asterless, is a Plk4 target that functions with Plk4 in centriole assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
288
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(319 citation statements)
references
References 38 publications
23
288
3
Order By: Relevance
“…Consistently, overexpression of Plk4 can promote the recruitment of Ana2/STIL and Sas-6 to supernumerary centrioles (Kleylein-Sohn et al 2007;Stevens et al 2010). A number of Plk4/ ZYG-1 substrates have been identified-SAS-6 (Kitagawa et al 2009), Cep152 (Hatch et al 2010), and a component of g-TuRC GCP6 (Bahtz et al 2012), but their significance is not clear. More recently, it has been shown in Drosophila that Plk4 phosphorylates Ana2 in its conserved STAN motif to enable it to bind to Sas-6.…”
Section: Plk4mentioning
confidence: 89%
See 2 more Smart Citations
“…Consistently, overexpression of Plk4 can promote the recruitment of Ana2/STIL and Sas-6 to supernumerary centrioles (Kleylein-Sohn et al 2007;Stevens et al 2010). A number of Plk4/ ZYG-1 substrates have been identified-SAS-6 (Kitagawa et al 2009), Cep152 (Hatch et al 2010), and a component of g-TuRC GCP6 (Bahtz et al 2012), but their significance is not clear. More recently, it has been shown in Drosophila that Plk4 phosphorylates Ana2 in its conserved STAN motif to enable it to bind to Sas-6.…”
Section: Plk4mentioning
confidence: 89%
“…One of these, Asterless (Asl, Drosophila)/Cep152 (vertebrates) has particular importance in recruiting Plk4 to the centrosome. The interaction of two of the Polo boxes of Plk4 (the cryptic Polo-box domain) with Asl/Cep152 is conserved in Drosophila, human, and Xenopus cells, although their codependency for localization differs (Cizmecioglu et al 2010;Dzhindzhev et al 2010;Hatch et al 2010). Asl also has additional roles in binding Sas-4 to help establish the PCM (see below).…”
Section: Plk4mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report showed that the Cep152 (1-217) fragment efficiently binds to Plk4 (21). Comparative analysis of primary amino acid sequences between Cep192 (201-280) and Cep152 (1-217) revealed that both fragments contained an N-terminal acidic (D/E) region and α-helix (or α-helix and acidic region for 1-217) motif and a C-terminal N/Q-rich motif (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that Cep152, a human ortholog of Drosophila Asterless, interacts with Plk4 through the CPB (20,21). However, the depletion of Cep152 does not significantly decrease the level of Plk4 at centrosomes.…”
mentioning
confidence: 99%